INFLUENCE OF REGULAR PRIMARY SCHOOL CURRICULUM ON QUALITATIVE CHANGES OF SEVENTH GRADE PUPILS' ANTHROPOMETRIC CHARACTERISTICS AND MOTOR ABILITIES - Dževad Džibrić; Haris Pojskić; Tarik Huremović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The aim of the study was to, based on Eurofit tests battery, which included eight motor tests and seven anthropometric instruments, evaluate qualitative changes pro- duced by standard primary school program for seventh grade pupils. Sixty six actually healthy primary school male pupils, from three classes, with ages 12 to 13 year partici- pated in this study. The obtained results showed qualitative changes of examined motor abilities and anthropometric characteristics, respectively, there were changes in num- bers of obtained factors, as well in factors' scores in the final testing comparing with initial assessment session. The stated hypothesis, that applied standard primary school program that was lasting for one school year, would produce qualitative changes of mo- tor abilities and anthropometric characteristics, was confirmed